On palaeomagnetic dating of fluvial deposits in the section of Neporotove gravel quarry on the Middle Dniester - Bondar Kseniia; Ridush Bogdan; Baryshnikova Mariia; Popiuk Yana (Днепропетровский национальный университет им. Олеся Гончара, 2019)
The paper presents the results of palaeomagnetic studies of Quaternary noncemented deposits from the section of Neporotove on the VIIIth terrace of the Dniester River valley with abnormal thickness (more than 20 m) of the channel alluvium near the village of Neporotove, located on the right bank of the Dniester River. Alluvial facies of river terraces’ deposits are valuable palaeogeographic archives but not quite complete. They are affected by denudation and often do not contain fossils. The possible way for their dating is provided by a palaeomagnetic method performed on suitable for sampling underlying and overlying beds. The alluvial sequence consists of four units. Unit I is composed of inclined gravel-pebble layers with the sand filler with a visible thickness of about 8 m. Unit II has bedded over the denudated surface of Unit I; it consists of light-yellow laminated aleurit loam, 5-30 cm thick underlaid by 0.5-1.5 bed of fine sand. We consider Unit II to be lacustrine deposits accumulated in quiet water. Unit III is represented with inclined or sub-horizontally layered gravel-pebble-boulder deposits with up to 10 m of visible thickness. It includes boulders and blocks of sedimentary rocks up to 1.0 in diameter, considered as drop-stones. In the roof of the gravel-pebble Unit III, there is the white carbonate layer, probably, the illuvial horizon of the palaeosol (mr1), which transited up into the brownish-red horizon A (Unit IV). Unit IV – dark-red sandy-gravel horizon, pedosediment, probably partly the reworked material washed into ice wages in the roof of Unit III. As a result of alternating field stepwise demagnetisation of natural remanence of sediments, we determined that loamy Unit II, which separates members of gravel stratum, and sandy Unit IV, which overlays packs of gravel alluvium, bear characteristic remanent magnetisation (RM) with normal geomagnetic polarity. Taking into consideration lithology and two-fold structure of terrace gravel alluvium as well as palaeomagnetic results, we assume the lacustrine deposits of Unit II was formed during Jaramillo palaeomagnetic subchron corresponding to the end of Shyrokyne Stage, and a pedosediment of Unit IV was formed during Martonosha Stage. The upper alluvial suite of a terrace (Unit III) was generally deposited during a cold stage, directly prior to the onset of lacustrine loam sedimentation, while the lower alluvial member (Unit I) dates from the preceding warm stage. Thus, we defined the geological age of the whole channel alluvium strata of the VIIIth Dniester terrace as Shyrokyne-Pryazovya Stage.
Keywords: Dniester River; Neporotove gravel quarry; river terrace; palaeomagnetic dating; channel alluvium; remanent magnetisation; річка Дністер; гравійний кар'єр Непоротове; річкова тераса; палеомагнітне датування; русловий алювій; залишкове намагнічення